Test-Retest Reliability of the Bod Pod: The Effect of Multiple Assessments. Issue 2 (April 2014) - Tucker, Larry A.; Lecheminant, James D.; Bailey, Bruce W.
The Bod Pod uses air-displacement plethysmography to estimate body fat percentage (BF%). This study was designed to assess the test-retest reliability of the Bod Pod. The study included 283 women ( M age =41.0 yr., SD = 3.0). Each participant was tested at least twice in the Bod Pod. Results showed no significant mean difference between the test and the retest. The intraclass correlation coefficient (ICC) was .991. However, the absolute value of the initial trial differences (absolute mean difference) was .96 ( SD = .90). A third assessment of BF% was taken when the initial trial difference was greater than 1 percentage point, and the two closest values were compared. This strategy resulted in a significant decrease in the absolute mean difference, from .96 to .55 percentage point, and ICC increased to .998. The Bod Pod appears to measure body fat percentage reliably; however, findings suggest that multiple trials may be necessary to detect small treatment effects.